Modeling of recloser operation schemes under system ground fault using EMTP-ATPDraw - T. Thanasaksiri (2018)
© 2014 IEEE. This paper simulates the operation of automatic circuit recloser under the system ground fault condition using MODELS language in transient digital simulation EMTP-ATPDraw. Any other recloser operation schemes such as two fast-one delay or one fast-one delay can be modeled. In this paper the recloser model has been tested with two fast and one time delay operation schemes for both temporary and permanent faults. The recloser model presented in this paper is the guideline for modeling the other recloser operation schemes including the other protective devices, such as fuse and over current relay which have the similar time-current characteristics.